Enhancing student visits through library strategies: A case study of SMKN 1 Percut Sei Tuan - Febriana, Amelia Dwi; Syam, Abdi Mubarak (Jurnal Informatio, 2025)
Background: The issue of low student interest in visiting the library is considered a crucial and urgent problem in the field of education. School libraries play a vital role in increasing student visit interest by providing various types of reading materials and other educational resources.Purpose: This study aims to identify, analyze, and evaluate the effectiveness of strategies implemented by the library of SMKN 1 Percut Sei Tuan in enhancing student visit interest, as well as to explore the supporting and inhibiting factors encountered.Methods: This qualitative case study explores the strategies, challenges, and opportunities of the SMKN 1 Percut Sei Tuan library. Data were obtained from five purposively selected informants through interviews, observations, and documentation, and analyzed using reduction, presentation, and conclusion drawing.Results: The library applied three strategies—social media promotion, friendly service, and collaboration with teachers—but these often overlooked key audience traits: vocational students’ pragmatic, instrumental, and goal-oriented mindset. Conclusion: The study reveals that the library of SMKN 1 Percut Sei Tuan employs strategies such as promoting collections through social media, providing friendly librarian services, and collaborating with teachers to increase student visit interest. Supporting factors include the enthusiasm of librarians and school support. Low student participation, lack of direct promotion, and limited collections serve as inhibiting factors. Therefore, strengthening strategies is necessary to further enhance student interest in visiting the library.